Scaling up antiretroviral therapy in Uganda: using supply chain management to appraise health systems strengthening - Windisch, Ricarda; Waiswa, Peter; Neuhann, Florian; Scheibe, Florian; de Savigny, Don (Globalization and health, 2011)
Strengthened national health systems are necessary for effective and sustained expansion of antiretroviral therapy (ART). ART and its supply chain management in Uganda are largely based on parallel and externally supported efforts. The question arises whether systems are being strengthened to sustain access to ART. This study applies systems thinking to assess supply chain management, the role of external support and whether investments create the needed synergies to strengthen health systems.
Gesehen am 07.11.2022